When the grits hit the fan - Day, Maddie (Day, Maddie. Country store mystery, 2017)
After hosting a dinner for Indiana University's Sociology Department at her restaurant, Pans 'N Pancakes, Robbie Jordan must flip over the clues to prove that her friend, graduate student Lou, did not kill Professor Charles Stilton, a man who seemed to thrive on heated exchanges with his students and peers before they all get burned.